The role of NBI HDTV magnifying endoscopy in the prehistologic diagnosis of laryngeal papillomatosis and spinocellular cancer - Lukes, Petr; Zabrodsky, Michal; Lukesova, Eva; Chovanec, Martin; Astl, Jaromir; Betka, Jaroslav A; Plzak, Jan (BioMed research international, 2014)
Narrow band imaging (NBI) HDTV (high definition television) magnifying endoscopy is considered to be superior for the accurate display of the microvascular patterns of superficial mucosal lesions. Observation of changes in intraepithelial papillary capillary loops (IPCL) can help distinguish benign from malignant lesions as part of an "optical biopsy." However, IPCL changes in papillomas may be mistaken for spinocellular cancer (SCC). The aim of the study was to determine whether observing microvascular changes alone is sufficient for discriminating between laryngeal SCC and papillomatosis. An additional aim was to identify associated characteristics that could clarify the diagnosis. The study included 109 patients with a suspected laryngeal tumor or papilloma. HDTV NBI magnifying endoscopy was performed during direct laryngoscopy. It was possible to visualize IPCL changes in 82 out of 109 patients (75.2%). In 71 (86.6%) patients, the diagnosis was correctly determined. In 4 (4.9%) cases, the diagnosis of SCC was expressed on the basis of finding pathologic IPCL, but histology did not demonstrate malignancy. To achieve a correct diagnosis using HDTV NBI magnifying endoscopy, it is important not only to observe changes in the shape of IPCL but also to note possible papillary structures with central-axis capillaries typical of papillomatosis.
Keywords: dospělí; Female; Narrow Band Imaging; Adult; ženské pohlaví; endoskopie; lidé; úzkopásmové zobrazení; Laryngeal Neoplasms; Aged, 80 and over; nádory hrtanu; Male; Aged; Endoscopy; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Papilloma; Middle Aged; papilom; Humans